Analysis of Green Building Implementation on the FEB and FP Buildings at Campus 1, Universitas Swadaya Gunung Jati - Ridwan Bakti; Rifal Aditya Pratama; Muhamad Fauzan; Fathur Rohman Robandi (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Using the Greenship Existing Building standard from the Green Building Council Indonesia (GBCI), this study assesses Green Building implementation in the FEB (Faculty of Economics and Business) and FP (Faculty of Agriculture) Buildings at Campus 1, Universitas Swadaya Gunung Jati. A quantitative-descriptive method was employed, with primary data from interviews, observations, and measurements of temperature, humidity, lighting, and airflow. Secondary data included building plans, water records, and operational documents. Results showed campus Green Open Space (RTH) at 31.94%, meeting Minister of Public Works Regulation No. 05/PRT/M/2008 (?30%). Average temperature (26.31°C) and humidity (53.09%) were comfortable, while lighting (394.418 lux) exceeded SNI 03-6197-2000 public area standards (100–300 lux). Water efficiency (6.44%) met basic needs but fell short of Greenship criteria. Energy intensity (1,413 kWh/year) surpassed SNI limits (?250 kWh/year), failing efficiency standards. Buildings excel in green space, thermal comfort, and lighting but need improvements in energy and water management to fully meet Greenship criteria. Recommendations: rainwater harvesting, energy-efficient equipment, and optimized operations aligned with sustainable campus principles.